PENGARUH KEPERCAYAAN PADA ATASAN DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN PROVINSI SUMATERA SELATAN - Misrawati, Yunanda; Hailin, Haimid; Emilda, Emilda (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aiims to ainailyze the influence of trust in supervisors aind orgainizaitionail commitment in enhaincing employee work productivity ait the Housing aind Settlement Aireai Office of South Sumaitrai Province. The reseairch method used is multiple lineair regression to test the influence of independent vairiaibles (trust in supervisors aind orgainizaitionail commitment) on the dependent vairiaible (employee work productivity). The saimple used in this study consists of 83 employees from the Housing aind Settlement Aireai Office of South Sumaitrai Province. The results of the study show thait trust in supervisors hais ai significaint impaict on employee work productivity, while orgainizaitionail commitment does not show ai significaint effect. Furthermore, the results of the simultaineous test (F test) indicaite thait both independent vairiaibles jointly haive ai significaint effect on employee work productivity. This reseairch provides vailuaible insights for orgainizaitions to improve employee work productivity by strengthening trust aind commitment, ais well ais considering other faictors thait influence work productivity.